ACANTAMOEBA KERATITIS-a case report - Celeva V.; Antova Velevska M.; Bron A. (Ophthalmological Society of Northern Greece, 1998)
Acanthamoeba keratitis still is a problem in ophthalmology because of diagnostic and therapeutic difficulties. To date, Acanthamoeba keratitis is an increasing pathology because of the more widespread use of the contact lenses. The patient was 22 year old myopic student, soft lens wearer. He complained of progressive pain and redness in his left eye since a week. The patient was unsuccessfully treated with topical antibiotics and steroids, including antiviral and antihistamininics. After three months, he complained redness and photophobia with comeal ulcer and Acantamoeba keratitis was suspected. Methods :the essential parasitological diagnosis was confirmed after comeal scarping inoculation onto agar with lown of Eschericia coli and morphological identification and according to the Pussard and Pons classification were done .A therapy with 0,02 PHMB for three months with prolonged decreasing dosage has begun with resolution of the infection. Conclusion: success factor for diagnosis and therapy are early identification of the parasite and the use of intensive therapy with 0,02%PHMB for considerable period of time.